Creep Behaviour of Fly Ash-Based Geopolymer Concrete - Wallah S.E. (Civil Engineering Dimension, 2010)
Fly ash-based geopolymer concrete is manufactured using fly ash as its source material and does not use Portland cement at all. Beside fly ash, alkaline solution is also utilized to make geopolymer paste which binds the aggregates to form geopolymer concrete. This paper presents the study of creep behaviour of fly ash-based geopolymer concrete. Four series of specimens with various compressive strengths were prepared to study its creep behaviour for the duration of test up to one year. The test method followed the procedures applied for Ordinary Portland Cement (OPC) concrete. Test results show that fly ash-based geopolymer concrete undergoes low creep which is generally less than that of OPC concrete. After one year of loading, the results for specific creep of fly ash-based geopolymer concrete in this study ranges from 15 to 29 microstrain for concrete compressive strength 67–40 MPa respectively. From the test results, it is also found out that the creep coefficient of fly ash-based geopolymer concrete is about half of that predicted using Gilbert’s Method for OPC concrete.